Brief report: Clinical implications of variant ALK FISH rearrangement patterns - Gao, Xin (J Thorac Oncol, 2015)
INTRODUCTION: Break-apart fluorescence in situ hybridization (FISH) is the FDA-approved assay for detecting anaplastic lymphoma kinase (ALK) rearrangements in non-small cell lung cancer (NSCLC), identifying patients who can gain dramatic benefit from ALK kinase inhibitors. Assay interpretation can be technically challenging, and either splitting of the 5′ and 3′ probes or loss of the 5′ probe constitute rearrangement. We hypothesized that there may be clinical differences depending upon rearrangement pattern on FISH. METHODS: An IRB-approved database of NSCLC patients at Dana-Farber Cancer Institute was queried for ALK rearrangement. Clinical characteristics and response to crizotinib were reviewed. Immunohistochemistry (IHC) and targeted next-generation sequencing (NGS) were obtained when available. RESULTS: Of 1,614 NSCLC patients with ALK testing, 82 (5.1%) patients had ALK rearrangement by FISH: 30 with split signals, 25 with 5′ deletion, and 27 with details unavailable. Patients with 5′ deletion were older (p=0.01) and tended to have more extensive smoking histories (p=0.08). IHC was positive for ALK rearrangement in all 27 patients with FISH split signals, while 3 of 21 patients with FISH 5′ deletion had negative IHC (p=0.05). Targeted NGS on 2 of 3 cases with discordant FISH and IHC results did not identify ALK rearrangement, instead finding driver mutations in EGFR and KRAS. Patients with 5′ deletion treated with crizotinib had a smaller magnitude of tumor response (p=0.03). CONCLUSIONS: Patients with 5′ deletion on ALK FISH harbor features less typical of ALK-rearranged tumors, potentially indicating that some cases with this variant are false-positives. Corroborative testing with IHC or NGS may be beneficial.